Ex vivo cultures and drug testing of primary acute myeloid leukemia samples: Current techniques and implications for experimental design and outcome. (December 2020) - Cucchi, D.G.J.; Groen, R.W.J.; Janssen, J.J.W.M.; Cloos, J.
Abstract: New treatment options of acute myeloid leukemia (AML) are rapidly emerging. Pre-clinical models such as ex vivo cultures are extensively used towards the development of novel drugs and to study synergistic drug combinations, as well as to discover biomarkers for both drug response and anti-cancer drug resistance. Although these approaches empower efficient investigation of multiple drugs in a multitude of primary AML samples, their translational value and reproducibility are hampered by the lack of standardized methodologies and by culture system-specific behavior of AML cells and chemotherapeutic drugs. Moreover, distinct research questions require specific methods which rely on specific technical knowledge and skills. To address these aspects, we herein review commonly used culture techniques in light of diverse research questions. In addition, culture-dependent effects on drug resistance towards commonly used drugs in the treatment of AML are summarized including several pitfalls that may arise because of culture technique artifacts. The primary aim of the current review is to provide practical guidelines for ex vivo primary AML culture experimental design.